AUDIT ENERGI UNTUK EFISIENSI ENERGI PADA GEDUNG PT. SEJAHTERA INDOBALI TRADA - Alit Sutresna, I Wayan; Ibi Weking, Antonius; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
PT. Sejahtera Indobali Trada is a car maintenance and sales service company. Excellent customer satisfaction is prioritized by this company. The best service must be done by using facilities effectively. For this reason, energy management is needed. Energy auditing is the first step in energy management. Energy audit to find out the use of electricity and opportunities. Energy audit includes the contents of energy data with available data and calculating Energy Consumption Intensity (IKE) based on the data collected. Previously, PT. Sejahtera Indobali Trada has never conducted an energy audit. This research method is done by calculating and comparing electrical energy in energy and energy systems. The results were obtained at 6.82% with the IKE difference between pre-audit and post-audit amounting to 0.59 kWh / m2 / month.